An indole-derived porous organic polymer for the efficient visual colorimetric capture of iodine in aqueous media via the synergistic effects of cation–π and electrostatic forces. Issue 9 (8th January 2020) - Huang, Min; Yang, Li; Li, Xiuyun; Chang, Guanjun
Abstract : A recyclable indole-based POP was successfully achieved, which was capable of visual colorimetric iodine capture in water via cation–π and electrostatic interactions. Abstract : We have successfully synthesized a novel type of recyclable indole-based porous polymer, which possesses highly effective capture behavior for iodine in aqueous solution via the synergistic effects of cation–π and electrostatic forces. More interestingly, the absorption performance can be efficiently detected via a visual colorimetric assay using a smartphone.